2022
DOI: 10.3389/fphar.2022.881231
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Glycyrrhetinic Acid on Lithocholic Acid-Induced Cholestatic Liver Injury Through Choleretic and Anti-Inflammatory Mechanisms

Abstract: Cholestasis is a clinical syndrome triggered by the accumulation and aggregation of bile acids by subsequent inflammatory responses. The present study investigated the protective effect of glycyrrhetinic acid (GA) on the cholestatic liver injury induced by lithocholic acid (LCA) from both anti-inflammatory and choleretic mechanistic standpoints. Male C57BL/6 mice were treated with LCA twice daily for 4 days to induce intrahepatic cholestasis. GA (50 mg/kg) and pregnenolone 16α-carbonitrile (PCN, 45 mg/kg) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…34 Elevated concentrations of LCA can the cause loss of intercellular junction proteins in hepatocytes, disrupt bile osmotic pressure gradients, reduce transmembrane movement of BAs, and ultimately accumulate in the liver, resulting in severe liver and gallbladder damage. 35 According to our findings, both DCA and LCA accumulated in the livers of ovariectomized hypercholesterolemic mice. However, after intervention with LP, the accumulation significantly decreased.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…34 Elevated concentrations of LCA can the cause loss of intercellular junction proteins in hepatocytes, disrupt bile osmotic pressure gradients, reduce transmembrane movement of BAs, and ultimately accumulate in the liver, resulting in severe liver and gallbladder damage. 35 According to our findings, both DCA and LCA accumulated in the livers of ovariectomized hypercholesterolemic mice. However, after intervention with LP, the accumulation significantly decreased.…”
Section: Discussionsupporting
confidence: 62%
“…LCA, a highly hydrophobic secondary BA, enhances the expression of the ASBT and is preferentially transported from the intestinal epithelium to hepatocytes . Elevated concentrations of LCA can the cause loss of intercellular junction proteins in hepatocytes, disrupt bile osmotic pressure gradients, reduce transmembrane movement of BAs, and ultimately accumulate in the liver, resulting in severe liver and gallbladder damage . According to our findings, both DCA and LCA accumulated in the livers of ovariectomized hypercholesterolemic mice.…”
Section: Discussionsupporting
confidence: 60%
“…DCA and LCA) were more effectively activate TGR5, which is expressed in Kupffer cells and hepatic stellate cells (HSCs) 51,52 . LCA is considered to be hepatotoxic as the most hydrophobic BA, 53 and it has been used to produce a model of cholestatic liver damage 54 . Serving as a physiological sensor of LCA, the pregnane X receptor (PXR) could be activated to protect against the LCA‐induced liver damage 55 .…”
Section: Discussionmentioning
confidence: 99%
“…51,52 LCA is considered to be hepatotoxic as the most hydrophobic BA, 53 and it has been used to produce a model of cholestatic liver damage. 54 Serving as a physiological sensor of LCA, the pregnane X receptor (PXR) could be activated to protect against the LCA-induced liver damage. 55 However, experimental data revealed that LCA and its derivatives inhibit HSC activation and have anti-inflammatory and anti-fibrotic effects by inhibiting The connecting lines between dots represent the correlation, with red lines referring to positive correlation, and green lines referring to negative correlation.…”
Section: Ba Changes and Their Associations With Liver Fibrosismentioning
confidence: 99%
“…Additionally, other hepatoprotective mechanisms are also discussed, such as the inhibition of the TLR/NF-κB pathway and upregulation of hepatic FXR to facilitate bile acid synthesis, transport, and detoxification, competitive inhibition of cyto P450 (CYP) enzymes responsible for the activation of pyrrolizidine alkaloid (PA) metabolism, particularly C3A1, which protects against liver damage, activation of PXR to regulate autophagy and lysosomal biogenesis, thereby alleviating acute liver injury, inhibition of hepatic stellate cell activation, and direct transcriptional inhibition of α2 (I) collagen gene (COL1A2), as observed in transgenic reporter mice, and other mechanisms. 147–150…”
Section: Antioxidant Activitymentioning
confidence: 99%